KELAYAKAN POSTER KANDUNGAN GIZI SEMANGKA YANG DIPERJUALBELIKAN DI KOTA PONTIANAK PADA SUB MATERI ZAT MAKANAN KELAS XI SMA - Pahlevi, Syarif Muhammad Riza; Daningsih, Entin; ., Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
This study aimed to know the feasibility of poster about watermelon (Citrullus vulgaris) nutrient content which were sold in Pontianak as a learning medium on sub material about nutrient in class XI SMA. This study method was descriptive with questionnaire as non-test collection data technique. Validation was done by the experts, they were 2 Biology Education lectures and 3 biology high school teachers in Pontianak. The technique of data analysis used Content Validity Ratio (CVR). The result of data analysis showed that the poster about watermelon nutrient content sold in Pontianak was feasible to use as a learning medium on sub material about nutrient in class XI SMA because all of assessment criteria had reached the minimum Lawshe CVR value (0.99). Keywords: Poster feasibility, Watermelon nutrient content.